2023
DOI: 10.3389/fonc.2023.1096386
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intensity modulated radiotherapy on lymphocytes in patients with esophageal squamous cell carcinoma and its clinical significance

Abstract: BackgroundRadiotherapy usually leads to a decrease in the total number of lymphocytes in patients with esophageal cancer. The factors that causing lymphopenia and the clinical significance of lymphopenia are studied in this article.Patients and methods110 patients with esophageal squamous cell carcinoma who had undergo intensity-modulated radiation therapy were enrolled. Statistical methods were used to analyze the correlation between lymphopenia and total survival in patients with esophageal cancer during rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“… 28 Recently, a study that included 110 ESCC receiving IMRT showed that radiation‐induced lymphopenia (RIL) was associated with cardiac and pulmonary dose parameters, and the results also demonstrated that RIL could predict survival and radiation pneumonia. 29 A meta‐analysis also revealed that RIL was associated with dosimetric factors such as PTV, cardiac dose, and effective dose to immune cells (EDIC), and it was correlated with lower pCR rates, as well as poorer OS and progression‐free survival (PFS). 30 However, none of them analyzed the pericardial dose.…”
Section: Discussionmentioning
confidence: 99%
“… 28 Recently, a study that included 110 ESCC receiving IMRT showed that radiation‐induced lymphopenia (RIL) was associated with cardiac and pulmonary dose parameters, and the results also demonstrated that RIL could predict survival and radiation pneumonia. 29 A meta‐analysis also revealed that RIL was associated with dosimetric factors such as PTV, cardiac dose, and effective dose to immune cells (EDIC), and it was correlated with lower pCR rates, as well as poorer OS and progression‐free survival (PFS). 30 However, none of them analyzed the pericardial dose.…”
Section: Discussionmentioning
confidence: 99%